The relationship between anxiety and sports performance perception of collegiate football athletes - Pagdanganan, Angelo T. 2002-; Kho, Edward del Prado (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Anxiety is common to sports, even among elite athletes. As the level of competition rises, anxiety will play a distinct role in an athlete’s performance because they are expected to win at great demands in order for them to succeed (Nayek & Chatterjee, 2013). This study focuses on identifying collegiate football athlete’s sport anxiety levels and sport performance perception, determining their relationship, and comparing the effects on female and male athletes. This study is limited to collegiate football athletes from a university that competed in the University Athletic Association of the Philippines (UAAP) Season 86. The Sport Competition Anxiety Test (SCAT) and Sport Performance Perception Scale (SPPS) were the used questionnaires in an online survey as the primary method of data gathering. SCAT was used to identify the sport anxiety levels and SPPS was used to identify the perception of sport performance under the sub dimensions of psychological skills and strategy & preparedness. Pearson’s correlation coefficient was used for data analysis with a level of significance of p < 0.05. The results show that all variables of sport performance perception have low to moderate negative correlation to sport anxiety with the collegiate football athletes. Female athletes exhibit higher sport anxiety levels than male athletes. Sport performance perception showed no drastic difference between male and female athletes. The p-value of all variables did not reach the level of significance, thus not rejecting the null hypothesis, making sport anxiety and sport performance perception among collegiate football athletes have no significant relationship
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Football players; Athletic ability; Anxiety; College athletes